2020
DOI: 10.3389/fendo.2019.00928
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Study of Oral Lichen Planus Associated With Thyroid Diseases in East China

Abstract: Objective: To investigate the prevalence of thyroid diseases in patients with oral lichen planus (OLP) and to explore the correlation between the two diseases. Methods: A cross-sectional study was conducted to investigate the history of thyroid disease in 585 patients with oral lichen planus diagnosed in the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 31 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…Numerous data come from the Chinese population, where a greater prevalence of TD, in particular HT, was found in patients with OLP [18][19][20] and the correlation between these conditions seemed to reside in common autoimmune pathways. 19 Current worldwide literature has shown that, among TD, hypothyroidism is the most frequently found condition in patients with a diagnosis of OLP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous data come from the Chinese population, where a greater prevalence of TD, in particular HT, was found in patients with OLP [18][19][20] and the correlation between these conditions seemed to reside in common autoimmune pathways. 19 Current worldwide literature has shown that, among TD, hypothyroidism is the most frequently found condition in patients with a diagnosis of OLP.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous data come from the Chinese population, where a greater prevalence of TD, in particular HT, was found in patients with OLP 18 19 20 and the correlation between these conditions seemed to reside in common autoimmune pathways. 19 …”
Section: Discussionmentioning
confidence: 99%
“…Muzio ( 20 ) reported the HT prevalence rate in patients with OLP was 14.29% (15/105) in Italy. Tang ( 26 ) reported that the prevalence was 12.14% (71/585) in East China. Zhou ( 24 ) reported that the prevalence was 20.83% (40/192).…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of studies have investigated the possible relationship between thyroid diseases (Hashimoto thyroiditis, hyperthyroidism, thyroid cancer, etc.) and OLP/OLL [13][14][15]. However, OLL coexisting with CD and papillary thyroid carcinoma (PTC) is very rarely described.…”
Section: Introductionmentioning
confidence: 99%